Failure - Decker, Scott H. (Criminology & public policy, 2024)
The Vollmer Award: The award honoring August Vollmer was first made in 1959. It is meant to recognize outstanding contributions to justice as well as scholarship and professional activity. I am honored to be the 2022 awardee because so many of the previous winners are individuals whose careers and work I have great respect for. Focus of My Remarks: This essay focuses on many failures in criminal justice policy and research. Costly though they may be, failures have the potential to teach us a good deal and we ignore them at our own peril.